SOCIAL CLASS CONFLICT IN PARASITE FILM - Muharomi, Anugrah Dwi; Mustikawati, Yunitari; Nur, Riola Haya (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
In this study, we analysed the social class conflict from the character statement and situation in the film. We analysed 2 problems; they are: (1) What type of class does each character include in the film according to social class conflict theory? (2) What causes the occurrence of conflict between social classes in the film according to social class conflict theory? The 2019 film Parasite was directed by Bong Joon-ho, who also co-wrote and co-produced it alongside Han Jin-won. This study employs a qualitative descriptive method combined with a sociological approach. Based on the findings, there are 3 types of social class, the lower class, the middle class, and the upper class. There are 4 characters for the lower class, 1 character for the middle class, and 2 characters for the upper class. The dynamics of each class are constantly overlapping and lead to issues such as the emergence of various conflicts. Each of the conflicts arises from the class differences among the characters in the film. The emergencies of the conflicts are varied, ranging from: conflict involving social positions, conflict of interest, and conflict of role.